Bioremediation of Bisphenol a and Benzophenone by Glycosylation with Immobilized Marine Microalga sp. - Kei Shimoda; Hiroki Hamada (SAGE Publishing, 2009)
Cultured cells of Pavlova sp. glycosylated bisphenol A to its mono-glucoside, 2-(4-β-D-glucopyranosyloxyphenyl)-2-hydroxyphenylpropane (9%). Use of immobilized Pavlova cells in sodium alginate gel improved yield of the product (17%). On the other hand, Pavlova cell cultures converted benzophenone into diphenylmethanol (49%) and diphenylmethyl β-D-glucopyranoside (6%). Incubation of benzophenone with immobilized Pavlova cells gave products in higher yields; the yields of diphenylmethanol and diphenylmethyl β-D-glucopyranoside were 85 and 15%, respectively.